Temporal Variability in Net Primary Production in an Upwelling Area off Central Chile (36°S) - Testa, Giovanni; Masotti, Italo; Farías, Laura (Frontiers in Marine Science, 2018)
The temporal variability of Net Primary Production (NPP) off central Chile (36ºS, 73ºW), an area subjected to seasonal coastal upwelling, was analyzed using monthly in situ 13C incubations within the photic zone, along with bio-oceanographic variables from a fixed time series station, and satellite NPP estimations (NPPE) from the Vertically Generalized Production Model between 2006 and 2015. NPP and NPPE rates varied from 0.03 to 18.29 and from 0.45 to 9.07 g C m-2 d-1, respectively. Both rates were fairly well correlated with each other (r2 = 0.61), but when these data were separated into two periods, higher r2 value was found during winter (r2 = 0.70) with respect to the rest of the year (r2 = 0.24); the latter correlation was partially due to increased weekly NPPE variability during active and relaxed upwelling events. NPP rates along with other biophysical variables allowed for a division of the annual cycle into three distinct periods: September to January (high productivity, mean integrated NPP rates of 4.0 g C m-2 d-1), February to March (intermediate productivity, mean integrated NPP rates of 1.4 g C m-2 d-1), and May to August (basal level, mean integrated NPP rates of 0.5 g C m-2 d-1). NPP appeared to be partially controlled by nutrient inputs, either from upwelling (September-April) and river discharge (May-August), maintaining high NPP rates throughout the entire year, with an annual mean NPP rate of 1.1 kg C m-2 yr-1. In this region, El Niño Southern Oscillation events do not appear to impact the NPP interannual variability.